Development and Characterization of as-cast Ti-20Ta-Nb Aiming Biomedical Applications - Marcia Almeida de Amaral Arcos da Silva; Israel Ramos Rodrigues; Giovana Collombaro Cardoso; Mariana Luna Lourenço; José Roberto Severino Martins Júnior; Pedro Akira Bazaglia Kuroda; Jaime Casanova Soeiro Junior; Carlos Roberto Grandini (Materials Research, 2025)
The present paper aims to develop and investigate Ti system alloys with the following weight compositions: Ti-20Ta, Ti-20Ta-10Nb, Ti-20Ta-20Nb, and Ti-20Ta-30Nb. These alloys are intended to contribute to the area of orthopedic implants. To achieve satisfactory results, thermodynamic simulations were performed using THERMOCALC software and molecular orbital theory to predict the crystalline phases of the metals. X-ray fluorescence characterizations, energy-dispersive X-ray spectroscopy, and density measurements were performed to verify the chemical composition of the alloys. The crystal structure was verified by X-ray diffraction, optical, and scanning electron microscopy techniques. Vickers microhardness measurements were performed to verify the influence of the crystalline phases on the metal's bulk hardness. The chemical composition results showed that the produced ingots have good quality, and the density results presented close theoretical and experimental values, indicating good chemical homogeneity. The X-ray diffraction measurements showed the following phases: the Ti-20Ta alloy is of the α” type. The addition of Nb in the alloys promoted the formation of β phases, demonstrating that niobium has β-stabilizing characteristics. Regarding the microhardness values, the Ti-20Ta-10Nb and Ti-20Ta-20Nb alloys presented the same hardness values (~ 298HV); the Ti-20Ta-30Nb composition has a lower hardness value (215HV) due to the formation of the β phase, which has a lower atomic packing factor.